Establishment of cavitation inception speed judgment criteria by cavitation noise analysis for underwater vehicles. (May 2021) - Jeong, Seung-Jin; Hong, Suk-Yoon; Song, Jee-Hun; Kwon, Hyun-Wung; Seol, Han-Shin
Cavitation occurs on objects that move underwater at high speeds, and it is accompanied by an increase in hull vibrations, a reduction in propulsion performance, and an increase in noise that is important for warships and submarines. Of the various types of cavitations, tip vortex cavitations (TVC) are the earliest occurring and are considered the most important in terms of cavitation inception speed (CIS). This study predicts the cavitation inception speed by conducting cavitation noise analyses. The trend of the noise according to the cavitation numbers before and after CIS was analysed, and the quantitative criteria to determine the CIS were presented through established procedures. The CIS value obtained through the analysis was verified by comparing it against the value obtained experimentally. The methods used to analyse the cavitation inception speed are developed using bubble dynamics for cavitation noises. First, flow-field information was obtained downstream of the wing to estimate the external force acting on the bubbles, and this was used to calculate the behaviour of the cavitation bubbles. The bubble dynamics analyses were performed for each cavitation nuclei by Lagrange approach to calculate the behaviour of the bubbles. The number of cavitation nuclei was calculated based on the density function with random placement upstream of the wing. The cavitation noise was analysed for various cavitation numbers, and the tendency of the noise generated for each case was investigated. The noise analysis results and the CIS predictions were compared and verified with the measured values in the Large Cavitation Tunnel (LCT) of the Korea Research Institute of Ship & Ocean Engineering (KRISO). Using these results, the effect of the tip vortex cavitation on the total flow noise was analysed, and CIS determination criteria using noise values was validated and established.